Factors Influencing Users’ Intention To Adopt Artificial Intelligence Cybersecurity Systems At Government And Semi-government Organizations In The United Arab Emirates - Alneyadi, Mohammed Rashed Mohammed Al Humaid Alneyadi (2023)
The revolutionising impacts of artificial intelligence (AI) on other fields have led to the realisation that the technology can improve cybersecurity and mitigate cybercrimes in both private and government organisations. However, this realisation has not contributed to the rapid adoption of cybersecurity systems in the UAE, despite the country being ranked as one of the nations that are quick to embrace emerging technologies. Against this background, this study investigated the factors that influence users' intention to adopt (ITA) AI cybersecurity systems at workplaces in the UAE. It drew upon a theoretical framework derived from the Protection Motivation Theory (PMT) and the Unified Theory of Acceptance and Use of Technology (UTAUT). This framework was extended by introducing new relationships and variables (AI knowledge, resistance to change, and job insecurity) to enhance its predictive power. A quantitative research approach and a correlational research design was adopted, whereby 340 questionnaires were administered to respondents chosen using the purposive sampling technique. These respondents comprised persons working in the IT department and/ or responsible for the cybersecurity of government and semi-government organisations in the UAE.